Assessing genetic diversity and performing genome-wideassociation studies (GWAS) using multiple marker types acrossdesi, kabuli, and wild accessions in chickpea (Cicer arietinum L.) - Ruperao, Pradeep; Vemula, A.K.; Valluri, Vinod Kumar; Manda, Sriswathi; Srivastava, Rakesh K.; Mayes, Sean; Varshney, Rajeev K.; Kudapa, Himabindu (Wiley, 2025)
Genetic diversity is a key aspect of the selection of superior genotypes in crop varietal improvement. Breeding activities in chickpea (Cicer arietinum L.) have successfully enhanced the genetic diversity by introducing variations from wild relatives and landraces. Such diversity was characterized by employing various molecular markers, including single nucleotide polymorphisms (SNPs), insertions and deletions (indels), presence/absence variations (PAVs), and so forth. These marker types through different studies provided different levels of genetic variations from single base to gene structure level. The use of multi-marker types for diversity analysis and genome-wide association studies (GWAS) represents a powerful strategy. In the current study, whole genome re-sequencing data from 593 select chickpea genotypes representing desi, kabuli, and wild types, with over 21 million SNPs, 10 million indels, and 16,117 PAVs, were analyzed. This study demonstrated enhanced diversity in both desi and kabuli types, with wild accessions showing higher diversity compared to landraces. A more comprehensive understanding and broader range of genetic diversity within and between desi, kabuli, and wild accessions, as well as landraces, cultivars, and breeding lines, were captured. The identified novel alleles and gene variations through this analysis offer effective breeding strategies for key traits such as yield, and biotic and abiotic stress tolerance that can significantly contribute to chickpea improvement. Overall, this study highlights the importance of balanced population design, use of multiple marker types in identifying diverse gene pool, and novel marker-trait associations for key/optimal traits paving the way for the development of more resilient chickpea varieties.